PROGRAM BUNDLING PRODUK SWB2P DALAM PERSPEKTIF SYARIAH (Studi Kasus BMT UGT Sidogiri CAPEM Cibitung) - Mamun, Sukron; Windyarti (Jurnal Ekonomi Syariah Pelita Bangsa, 2021)
Indonesia, which is the country with the largest number of Muslims in the world, based on Globalreligiusfuture data, in 2020 it is estimated that the Muslim population in Indonesia will reach 229.62 million. With this sizeable growth it also encourages the development of syari'ah financial institutions in Indonesia, one of which is BMT UGT Sidogiri. Baitul Maal Wat Tamwil which first started operating on June 6, 2000 or 5 Rabiul Awal 1421H has a very noble mission, which is to eradicate usury in the community. One of them is by having a product in their savings, namely the MDA SWB2P term savings where people can save their funds for a certain period of time and can have reciprocity in the form of umrah, motorized vehicles or electronic goods directly without having to go into debt with an interest system. In this study, the authors used a qualitative approach which is research based on facts. The writer is a key instrument in obtaining data. The dominant method is the method of interviewing, observing and summarizing the opinions of scholars from social media and elaborated through writing. Data collection techniques in this study are using observation methods, interview methods (interview) and documentation methods. The analysis technique used in this research is descriptive qualitative data analysis with a case study approach. From the results of this analysis, BMT UGT Sidogiri explained that the SWB2P term MDA savings is one of BMT's efforts to eradicate loan usury which is now mushrooming in the community, be it motor vehicle loans or electronic goods. With the combination of the wadi'ah yad dhamanah contract and the murabahah contract on product bundling, it is hoped that customers will be interested in investing while eradicating usury.